La señorita Mapp - Benson, E. F. 1867-1940 (Impedimenta, 2013)
Miss Elizabeth Mapp, magnificent, grande dame and heiress, is always on the lookout lest her neighbors fall outside the bounds of perfect, exemplary manners. But her tightly controlled world is soon beset on all sides by interlopers, first in the disturbingly masculine form of two very different retired army officers, both of whom are anything but retiring in their conflicting aims upon her heart.